Macromycetes indicator species for xerothermic grasslands of the Chęciny district - Justyna Jaworska; Janusz Łuszczyński; Bożena Łuszczyńska; Agnieszka Tomaszewska (Acta Agrobotanica, 2012)
In the Chęciny district, xerothermic grasslands developed on deforested slopes of limestone hills, truncated folds, and mounds. Their origin is directly connected with agricultural and pastoral farming of man. Xerothermic grassland belongs to the class Festuco-Brometea, and the alliance Cirsio-Brachypodion. The plant association Thalictro-Salvietum pratensis is the most widespread in this area. The xerothermic grasslands have their own characteristic biota of macromycetes. The following steppe, xerothermic, and thermophilous fungi deserve special attention: Agaricus bernardii, Camarophyllus virgineus, Conocybe sienophylla, Entoloma incanum, Hygrocybe konradii, H. persistens, H. reae, Lepiota alba, and Leucopaxillus lepistoides. As a result of the xerothermic swards being progressively overgrown by shrubs and trees, among others, by Pinus sylvestris, one can find fungi species accompanying this tree: Suillus collinitus, also fungi producing underground fruit bodices Rhizopogon obtextus and Rh. roseolus. The main factors threatening xerothermic grasslands of the Chęciny district are, among others, the devastation and disappearance of natural habitats, often as a result of inappropriate human land management as well as the pollution of air, water, and soil. The effective protection of rare, threatened, and also legally protected fungi species is only possible by protecting their natural habitats as a whole.